Pembelajaran berbasis proyek pembuatan sabun dari minyak jelantah bagi siswa SMP Muhammadiyah La’joa, Kabupaten Soppeng, Sulawesi Selatan - Andi Zulfikar Syaiful; Ridwan Ridwan; Imaduddin Imaduddin (Riau Journal of Empowerment, 2026)
Efforts to reduce environmental pollution must be made by all parties, including schools, by providing environmental education to their students from an early age. This activity aims to increase students' knowledge and skills in handling used cooking oil waste and processing it into soap, as well as to enhance the environmental, scientific, and digital literacy of SMPM La'joa students. The Module for Making Used Cooking Oil Soap is prepared as a reference for the Project-Based Learning that will be carried out. There was a 74% increase in students' environmental knowledge and a 66% increase in their soap-related science knowledge. All student groups made solid soap using the cold process method, following the correct soap-making stages. This project is expected to positively influence students' pro-environmental attitudes and behavior, enabling them to play an active role in addressing waste management problems and creating environmentally friendly products.